2014
DOI: 10.1002/fld.3932
|View full text |Cite
|
Sign up to set email alerts
|

A method for computing curved meshes via the linear elasticity analogy, application to fluid dynamics problems

Abstract: SUMMARYWe propose and analyze an algorithm for the robust construction of curved meshes in two and three dimensions. The meshes are made of curved simplexes. The algorithm starts from a mesh made of straight simplexes, and using a linear elasticity analogy applied on well‐chosen data, one can generate a curved mesh. Note that if the initial mesh has a boundary layer, this method allows to conserve it on the final mesh. This algorithm is used on several airfoils in two and three dimensions, including a turbulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Hierarchical methods proceed to curve edges first, then faces, then elements [Ziel et al 2017] although behavior on complex 3D domains has not been demonstrated. Arguably, the most successful family of curved meshing methods rely on a mechanical analogy: these optimization-based methods use an initial straight-edge mesh as a reference domain and minimize a non-linear distortion using FEM between the reference domain and the parametric elements, thus effectively computing an elastostatic solution where the distortion they target defines a potential energy of deformation [Abgrall et al 2012;Johnen et al 2013]. However, the non-linearity of the potential is often an obstacle to finding a good minimum, and starting from a straight-edge mesh of the domain unnecessarily adds distortion if this mesh is not of high quality.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchical methods proceed to curve edges first, then faces, then elements [Ziel et al 2017] although behavior on complex 3D domains has not been demonstrated. Arguably, the most successful family of curved meshing methods rely on a mechanical analogy: these optimization-based methods use an initial straight-edge mesh as a reference domain and minimize a non-linear distortion using FEM between the reference domain and the parametric elements, thus effectively computing an elastostatic solution where the distortion they target defines a potential energy of deformation [Abgrall et al 2012;Johnen et al 2013]. However, the non-linearity of the potential is often an obstacle to finding a good minimum, and starting from a straight-edge mesh of the domain unnecessarily adds distortion if this mesh is not of high quality.…”
Section: Previous Workmentioning
confidence: 99%
“…Our use of a reference domain with unit elements is quite different from any of the other methods anchored in continuum mechanics such as [Abgrall et al 2012;Bargteil and Cohen 2014;Johnen et al 2013;Persson and Peraire 2009] as they all use non-unit straightedge triangulations as reference, which unnecessarily biases the notion of isotropy based on the quality of the tetrahedron mesh they start from. Instead, our interpretation phrases the optimization as a minimization of distortion with respect to a perfect mesh.…”
Section: Odt As Elastostaticsmentioning
confidence: 99%
“…Most of them involve the ratio of minimum to maximum Jacobian in each element [8,10,11,12,13,14], the ratio of the minimum Jacobian to the Jacobian of the corresponding straight-sided element [1] or the integral of the Jacobian divided by the Jacobian of the straight-sided element [15].…”
Section: Detection Of Invaliditiesmentioning
confidence: 99%
“…A more robust method may be obtained by using non-uniform material properties, that is by using stiffer material in small elements near curved boundaries. More successful strategies have been proposed, including a nonlinear mechanics formulation [14] and an iterative method working on the Bézier control points of the elements instead of the Lagrangian nodes [12].…”
Section: Regularization Of Invalid Meshesmentioning
confidence: 99%
“…The initial approach proposed in [58] used a non-linear neoHookean constitutive model. Several attempts to reduce the computational cost of this approach have been proposed based on a linear elastic analogy, see [1,77]. It is clear that when large deformations are induced to produce the deformed curvilinear high-order mesh, a linear elastic model can result in non-valid elements due to the violation of the hypothesis of small deformations.…”
Section: Introductionmentioning
confidence: 99%